On-board-shell measurements of acceleration - Young, K; Muirhead , R.
Rowing Performance as indicated by the acceleration profile of the shell and the rowing seat may be a sensitive diagnostic tool for the development and the teaching of good rowing. The thrust of the drive and the smoothness of the recovery are shown in extremely good detail by using on-board accelerometers on the rowing shell and the rowing seat. The qualitative measurements can yield some discoveries of the hydrodynamics of rowing. The quantitative measurements can also be used to verify the models of rowing. Further uses would be verify the efficacy of rowing styles and experimental equipment like rigging or of oars. The advent of good and rugged solid state accelerometers, and special purpose logging computers make this a practical device for field use. Discussion: Direct acceleration measurements by solid state accelerometer is practical. Strength and smoothness of rowing are demonstrated. Consistency of strokes are easily seen. Mystery dip at about 70 to 90 degrees. Speculation 1. Scull blade is stalled. Transition of leg to upper body drive is not continuously high. Conclusion: Solid state accelerometer measurements are useful for rowing development. Mystery dip in acceleration curve during stroke suggests experiments to determine cause. Answer may suggest improvements in rowing geometry in the rigging and the blade shape. The acceleration profile can easily be used to monitor performance during pieces and races. It can be used to help diagnose the start, the beginning, the sprint etc.